3x-11=45-5x

Simple and best practice solution for 3x-11=45-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-11=45-5x equation:


Simplifying
3x + -11 = 45 + -5x

Reorder the terms:
-11 + 3x = 45 + -5x

Solving
-11 + 3x = 45 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-11 + 3x + 5x = 45 + -5x + 5x

Combine like terms: 3x + 5x = 8x
-11 + 8x = 45 + -5x + 5x

Combine like terms: -5x + 5x = 0
-11 + 8x = 45 + 0
-11 + 8x = 45

Add '11' to each side of the equation.
-11 + 11 + 8x = 45 + 11

Combine like terms: -11 + 11 = 0
0 + 8x = 45 + 11
8x = 45 + 11

Combine like terms: 45 + 11 = 56
8x = 56

Divide each side by '8'.
x = 7

Simplifying
x = 7

See similar equations:

| 5y+36=-6-2y | | 45x=5x-10 | | 6(-3v+1)= | | 9(12x+15)=50 | | 5-5p=2p+7 | | B+1=b+6 | | 42=8a-2a+12 | | 5.5-x=4.5-x | | 7n-18=5n+6 | | -40+16=3m+6 | | 8x+2x-4=6 | | 0=0.28[(21952)(-t^3)] | | 3.2b-33.4=75.1 | | 13w-11w=3-w | | 2.4=2h | | 4(x-6)+8=6x-2 | | 9t-6+-6t=6 | | 3x-4(2x-3)=18-8x | | 50k+60=40k+80 | | (9a+28)+(10a)=180 | | z-86=-4 | | x=27.5 | | d-8=-17 | | 34+x=109 | | 6p-2-3b=16 | | 14m^2+2m=0 | | (5a+10)+(3a+10)=180 | | -h/6+1=-1 | | 2[X+2]-X=3[X+1]+9 | | 3b-4+b=8 | | 17a=3a+7 | | -2(b+4)= |

Equations solver categories